The Role of Knowledge and Trust in Explaining Intention of Performing Waqf in Agricultural Sector - Sunarmo, Sunarmo; Majid, Rifaldi (Universitas Muhammadiyah Yogyakarta, 2024)
This research aimed to analyze the influence of trust and waqf knowledge (WK) on intention to make endowment for programs in agricultural sector using Partial Least Square-Structural Equation Modeling (PLS-SEM) with 4th edition of SmartPLS analytical tool. In addition, the questionnaire was adopted from previous analyses and filled in by 100 respondents familiar with waqf. The results showed that three variables, which were components of Theory of Planned Behavior (TPB), namely subjective norm (SN), attitude toward behavior (ATB), and perceived behavioral control (PBC) had a significant influence on intention to perform waqf in agricultural sector. Regarding the main result, ATB mediated the role of trust and waqf knowledge for waqf. The results had implications for the importance of increasing waqf literacy for all levels of society by presenting religious leaders and increasing nazhir's professionalism in managing funds.